Advantage of laparoscopic resection for pelvic Schwannoma: Case report and review of the literature. (2018) - Di Furia, Marino; Salvatorelli, Andrea; Della Penna, Andrea; Vicentini, Vincenzo; Sista, Federico; Chiominto, Alessandro; Guadagni, Stefano; Clementi, Marco
Highlights: Retroperitoneal schwannomas are usually asymptomatic, rare neoplasms. Diagnosis can only be achieved with surgical removal of mass. Laparoscopy is the most useful therapeutic approach. Abstract: Introduction: Single pelvic schwannomas are rare tumor arising from the retrorectal, lateral or obturatory space. Laparoscopic approach to schwannoma located in lateral pelvic space has been previously described only in one case report. We present a case of a successful laparoscopic resection of pelvic schwannoma emphasizing the advantages of such a minimal invasive approach. Presentation of case: A 54-years-old, obese, male patient was admitted to our hospital referring dysuria and strangury. Abdominal CT scan showed a lateral pelvic well-circumscribed mass with smooth regular margins. A CT-guided fine needle biopsy resulted non-diagnostic. An elective laparoscopic resection was performed. The patient had a short, uneventful post-operative course. Pathological examination revealed a benign schwannoma. Discussion: Using PubMed database, we reviewed the English language international literature using the MeSH terms "laparoscopic, " "minimally invasive" and "schwannoma". We identified quite 20 previous cases of pelvic schwannomas removed by laparoscopy or robotic surgery. We found out that a preoperative diagnosis of these rare neoplasms is difficult to be obtained; in most cases, laparoscopic approach was successfully performed. Conclusion: Despite it could not be proven yet, due to the rarity of this tumor, we agree with literature that laparoscopic removal of pelvic benign tumor may offer several advantages. The direct high-definition vision deeply into this narrow anatomical space, especially in obese patients, provides a detailed view that makes easier to isolate and spear the anatomical structures surrounding the tumor. Furthermore, the pneumoperitoneum may create the right plane of dissection, minimizing the risk of tumor rupture and bleeding.